Reshaping identities: The second generations of immigrants in Zadie Smith’s White Teeth (2000) and Zia Haider Rahman’s In the Light of What We Know (2014) - Alam, Musrat (Brac University, 2022)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2022.